Institutes for the new model of economic growth regional management development (territories of advanced development, territories of advanced social and economic development) - N. S. Stepanov (Вестник университета)
The article describes the importance of institutions for the development of regional governance of a new model of economic growth, presenting both the tasks and the organizational structure of the main actors of development policy, as well as the nature of the relationship between the main actors and their cooperation with other external partners, such as public institutions, institutions of the business environment and individual international institutions. It is substantiated that the allocation of zones with a special legal status on the territory of the state is always associated with the need for appropriate institutional support. In the field of territories of advanced development, there is a separate regulation that changes the generally applicable rules of law concerning the beginning and implementation of economic activity. The instrument of this regulation is the functioning of institutions for the development of regional governance, which provide favorable conditions for doing business on special preferential terms. The creation by the state of special conditions for economic activity in relation to selected investors in this territory serves the primary purpose of accelerating the socio-economic development of certain parts of the country’s territory. The new model of economic growth in the form of territories of advanced development provides an increase in investment activity, intensification of foreign economic activity, reduction of regional differentiation.